2016
DOI: 10.1016/j.nedt.2015.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of clinical competence by simulation, a hermeneutical observational study

Abstract: Making the transition from theory to practise easier in nursing education through simulation is widely implemented all over the world, and there is research evidence of the positive effects of simulation. The pre-understanding for this study is based on a definition of clinical competence as encountering, knowing, performing, maturing and developing, and the hypothesis is that these categories should appear in simulated situations. The aim of the study was to explore the forms and expressions of clinical compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The notions of caritas and caritative caring have influenced the education of nursing teachers at Åbo Akademi University, the Alma Mater of caring science in Finland. Articles on nursing education from a caritative perspective have been written by, among others, Matilainen and Westerlund‐Perätalo (2001), Sandvik, Eriksson, and Hilli (2015), Lejonqvist, Eriksson, and Meretoja (2016), and Ekebergh, Andersson, and Eskilsson (2018).…”
Section: Implications For Nursingmentioning
confidence: 99%
“…The notions of caritas and caritative caring have influenced the education of nursing teachers at Åbo Akademi University, the Alma Mater of caring science in Finland. Articles on nursing education from a caritative perspective have been written by, among others, Matilainen and Westerlund‐Perätalo (2001), Sandvik, Eriksson, and Hilli (2015), Lejonqvist, Eriksson, and Meretoja (2016), and Ekebergh, Andersson, and Eskilsson (2018).…”
Section: Implications For Nursingmentioning
confidence: 99%
“…These study results supported by a study on the evidence of clinical competence by simulation revealed that clinical competence could be made evident and developed by simulation. 10 Another similar finding in a study on baccalaureate nursing students' preceptorship program and the development of clinical competence revealed that students who participated in preceptorship program gained more level of clinical competence than the students who worked as nursing assistants in a noninstructional clinical setting. 11…”
Section: Discussion Of the Study Findingsmentioning
confidence: 67%
“…22 There is, however, some evidence to suggest actors can enhance the benefits of simulation in achieving enhanced perceived self-efficacy, clinical competence, and improved communication skills. [22][23][24] Taking simulation a step further, an approach to simulation named "Mask-Ed" was developed to create a more realistic experience for students, allowing encounters with "consumers" to be recreated in a safe environment. 25 The educator wears a silicon mask and creates a character with specific health issues and other characteristics preselected as the focus of student learning.…”
Section: Introductionmentioning
confidence: 99%